Physical activity, pain interference and comorbidities relate to PROMIS physical function in younger adults following total knee arthroplasty. Issue 26 (18th December 2021) - Christensen, Jesse; Peters, Christopher; Gililland, Jeremy; Stoddard, Gregory; Pelt, Christopher
Abstract: Purpose: To determine if preoperative physical and psychological health risk factors are influential on physical function and satisfaction scores in a cohort of relatively younger adults one year post-total knee arthroplasty. Methods: Sixty-five patients were recruited pre- and one year post-total knee arthroplasty. Physical (i.e., body mass index, sex, physical activity level, number of comorbidities) and psychological (i.e., depression, expectations, pain inference) health risk factors were obtained pre-total knee arthroplasty and compared to Patient-Reported Outcomes Measurement Information System physical function computerized adaptive testing and satisfaction scores one year post-total knee arthroplasty. Results: Bootstrap inclusion fraction methods were performed to compare the stability of each predictor variable prior to final regression analyzes. Poorer preoperative physical activity level (standardized regression coefficient = 0.37; p < 0.01), pain interference (standardized regression coefficient = –0.24; p = 0.03) and greater comorbidities (standardized regression coefficient = –0.27; p = 0.01) resulted in worse physical function scores one year post-total knee arthroplasty. Greater preoperative comorbidities (odds ratio = 0.63; p < 0.01) resulted in worse satisfaction scores one year post-total knee arthroplasty. No other predictor variable had any relationship on either clinical outcome ( p > 0.05). Conclusion: Younger adults with greater comorbidities, lower physical activity level and higher pain interference scores preoperatively reported poorer functional recovery one year post-total knee arthroplasty. Understanding how preoperative status of younger adults undergoing total knee arthroplasty may lead to better improved surgical decision making and health care delivery for this vulnerable and growing patient subgroup. Implications for Rehabilitation: Projections estimate total knee arthroplasty in relatively younger adults (<65 years) will make up the majority of surgical procedures performed in the United States within the next two decades, however little is known in this patient population. This study provides evidence that relatively younger adults with greater comorbidities, lower physical activity level and higher pain interference scores preoperatively result in poorer functional recovery one year post-total knee arthroplasty. The results also suggest greater comorbidities identified preoperatively have the largest influence on one year satisfaction scores in younger adults post-total knee arthroplasty. Modifiable characteristics such as improving physical activity level, incorporating pain management strategies and reducing comorbidities preoperatively or adopting into postoperative rehabilitative care may influence the postoperative physical function and satisfaction scores in relatively younger adults undergoing total knee arthroplasty.